Gastrointestinal sarcoidosis mimicking malignancy: A confusing scenario - Dilara Bulut Gokten; Ridvan Mercan (Caspian Journal of Internal Medicine)
clinicians should consider the possibility of GI sarcoidosis in patients presenting with systemic symptoms of malignancy, even in the absence of pulmonary involvement.